2018
DOI: 10.1148/radiol.2017170553
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Kurtosis Imaging of Acute Infarction: Comparison with Routine Diffusion and Follow-up MR Imaging

Abstract: Purpose To determine the relationship between diffusion-weighted imaging (DWI) and diffusion kurtosis imaging (DKI) in patients with acute stroke at admission and the tissue outcome 1 month after onset of stroke. Materials and Methods Patients with stroke underwent DWI (b values = 0, 1000 sec/mm along three directions) and DKI (b values = 0, 1000, 2000 sec/mm along 20 directions) within 24 hours after symptom onset and 1 month after symptom onset. For large lesions (diameter ≥ 1 cm), acute lesion volumes at DW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 34 publications
6
35
0
Order By: Relevance
“…Notably, the CNR of MRAPTR maps determined from CW‐ and pulse‐APT MRI were not significantly different from each other (3.59 ± 0.40 vs. 3.25 ± 0.65, P > .05). As such, highly pH‐specific pulse‐APT MRI is feasible with the generalized MRAPT analysis, which is promising for characterizing the heterogeneous ischemic tissue injury typically characterized by perfusion and diffusion MRI …”
Section: Discussionmentioning
confidence: 99%
“…Notably, the CNR of MRAPTR maps determined from CW‐ and pulse‐APT MRI were not significantly different from each other (3.59 ± 0.40 vs. 3.25 ± 0.65, P > .05). As such, highly pH‐specific pulse‐APT MRI is feasible with the generalized MRAPT analysis, which is promising for characterizing the heterogeneous ischemic tissue injury typically characterized by perfusion and diffusion MRI …”
Section: Discussionmentioning
confidence: 99%
“…The swelling and structural destruction of organelles make the water molecule diffusion more limited. The MK value is a more sensitive indicator of damage than the MD value, which suggests that the former can be used to represent the microenvironment complexity index and water molecule heterogeneity in the tissues 16,18,28,29 . In calculating the rate of change of MK and MD values, and to avoid bilateral infarction and the complication of side infarction and the influence of the contralateral perfusion pressure increase, we used measurements in a normal control group, which provided a more accurate scale for lesion evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusional kurtosis imaging (DKI) has been introduced to measure the degree of non‐Gaussian displacement in disorders such as Parkinson's disease, epilepsy, traumatic brain injury, and stroke . In particular, emerging evidence has suggested that the kurtosis lesion likely provides greater specificity for the infarction core than the routine DWI lesion .…”
Section: Introductionmentioning
confidence: 99%